Burden of allergic rhinitis and impact of MP-AzeFlu from the patient perspective: pan European patient survey. (3rd July 2021) - Canonica, G. Walter; Klimek, Ludger; Acaster, Sarah; Dollner, Ralph; Kaulsay, Ranbir; Lo, Siu Hing; Price, David B.; Scadding, Glenis K.; Valovirta, Erkka; Zieglmayer, Petra
Abstract: Objective: The aims of this survey were to (1) assess the burden of allergic rhinitis (AR) from the patient perspective, (2) investigate MP-AzeFlu use in real life and its impact on patients' lives and (3) explore factors associated with treatment satisfaction. Methods: A cross-sectional, quantitative, online, questionnaire-based survey was conducted in seven European countries (March–June 2019). Questions explored AR burden and treatment satisfaction. Satisfaction was assessed using the Treatment Satisfaction Questionnaire for Medication 9-item (TSQM-9; max score = 100). Participants (aged ≥18 years) had a doctor/healthcare provider confirmed AR diagnosis and used MP-AzeFlu within the last year. Results: Pre-MP-AzeFlu treatment, participants ( n = 1004) reported an average of 3.3 (SD:3.5) doctor visits/year, 8.1 (SD:11.0) days/year absenteeism and 15.8 (SD:18.9) days/year presenteeism due to AR. Only 48% of participants used MP-AzeFlu twice/day as recommended. Post-MP-AzeFlu 57% of participants reported better QoL, 47% reported fewer doctor visits and 52% discontinued polypharmacy. Absenteeism and presenteeism were reduced by 2.5 (SD 10.0) and 7.3 (SD:16.0) days/year, respectively. 70% of participants were more/much more satisfied with MP-AzeFlu versus previous AR treatment(s), and ≥70% were satisfied/extremely satisfied with its ability to prevent/treat AR, relieve symptoms and with its onset of action. Mean global, effectiveness and convenience TSQM-9 scores were 70.0 (SD:19.8), 68.3 (SD:21.6) and 72.7 (SD:20.4), respectively. Treatment satisfaction and effectiveness were significantly improved when MP-AzeFlu was taken as recommended. Conclusions: The impact of AR on patients' lives remains high. Real-life use of MP-AzeFlu reduces that impact and is associated with a high level of effectiveness, convenience and global satisfaction.